Going, Going, Gone: Devastation in Antakya - Corbett, Glenn J. (The Biblical archaeology review, 2024)
In February 2023, southern Turkey and northern Syria were hit by a series of powerful earthquakes that laid waste to much of the region. The loss to life, livelihoods, and property has been nearly incalculable: The earthquakes killed tens of thousands, displaced millions, and leveled entire cities and towns. The city of Antakya, built on […]